Resistance of lettuce downy mildew’s differential cultivars to root-knot nematodes - Vidal, Roberta L.; Soares, Renato S. [UNESP]; Kobayashi, Bruna F. [UNESP]; Franco, Carolina A. [UNESP]; Marin, Marcus V.; Soares, Pedro L.M. [UNESP]; Maldonado-Junior, Walter [UNESP]; Braz, Leila T. [UNESP] (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2019)
Due to the harmful potential and existence of numerous races of lettuce downy mildew (Bremia lactucae Regel), several countries carry out the monitoring of these races through the use of differential cultivars of lettuce (Lactuca sativa L.) The identification of resistance to other important diseases in these cultivars would be of great value for the lettuce’s breeding, allowing the simultaneous selection for diseases. Among soil pathogens, the most important are the root-knot nematodes (Meloidogyne spp.) due their damage and difficulty of control. Thus, the present work evaluated the resistance of these differential cultivars (C-Set) against the two most important nematode species for the crop, M. javanica and M. incognita. The experiment was conducted in a completely randomized design, with eight replicates and initial population of 1000 eggs and juveniles. The evaluations were performed by the criteria of reproduction factor and reproduction index, 75 d after inoculation. Data were submitted to ANOVA and averages were compared by the Scott-Knott test (p < 0.05). All cultivars are considered susceptible to M. incognita by the reproduction factor, ‘Argelès’, ‘Bedford’, ‘Design’ and ‘Grand Rapids’ are considered as slightly resistant by the reproduction index. However, to M. javanica ‘Argelès’, ‘Kibrille’, ‘Balesta’, ‘Colorado’, ‘Design’, ‘Bartoli’, and ‘NunDm15' are classified as resistant by the reproduction factor and very resistant by the reproduction index, and can be used as resistance source for simultaneous selection to downy mildew and this species of nematode.
Keywords: Breeding; Bremia lactucae; Lactuca sativa; Meloidogyne spp.; Resistance genes